Philosophical Foundations of Physical Education and Sport Applied to University Students of Central Areain Iraq According to the Social Understanding - Haider Abbas Abdul Amir1 , Murtaza Ali Shaalan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The study objectives: To recognize the reality of understanding the members of the research community incentral Iraq for physical education and sports. Building foundations for the philosophy of physical educationand sports in Iraq according to the social understanding. Research hypotheses: There is a possibility toidentify the reality of understanding the members of the research community for physical education andsports of universities in central area in Iraq. The research methodology included, where the researchers usedthe descriptive approach and survey studies for their suitability to the research problem and its objectives. Theresearch sample consisted of (200) male and female students from the Iraqi Middle Euphrates universitiesafter distributing a questionnaire to the research sample consisting of (60) questions to solve the problemnoting that the questionnaire is scientifically evaluated and it has been proven. After collecting the answersof the research sample, the researchers presented these results by using statistical means, analyzing thoseresults, and then discussing it , and the research objectives were fully achieved.